Dampak Pembelajaran Daring Terhadap Perkembangan Sosio-Emosional Peserta Didik - Maulana Ilyas As'ari; Raden Rachmy Diana (Nusantara: Jurnal Pendidikan Indonesia, 2022)
The COVID-19 pandemic has forced the education process to be carried out online. Online education has a varied impact on the socio-emotional development of students. This study will analyze the impacts of online education on students' socio-emotional development. This research uses the library research method (library study). The data in this research are taken from literature or documents in the form of journals, books, articles, etc. that examine the impact of online education on the socio-emotional development of students. The results of this study indicate that the impact of online education on the socio-emotional development of students is different. Some of the effects of online education on the socio-emotional development of students are children who are less cooperative, children who are less sociable, the emotions of children who sometimes feel bored, and children who miss their classmates and teachers.